Diversity of the W1 gene encoding flavonoid 3′, 5′-hydroxylase in white- and purple-flowered soybeans. Issue 3 (8th December 2014) - Park, Gyu Tae; Sundaramoorthy, Jagadeesh; Park, Jong-Beum; Lee, Jeong Dong; Choi, Kwang Shik; Kim, Jeong Hoe; Seo, Hak Soo; Park, Soon-Ki; Song, Jong Tae
Abstract : Cultivated soybeans [ Glycine max (L.) Merr.] have various flower colours such as dark purple, purple, light purple, pink, magenta, near white and white. About one-third of the soybean accessions in the United States Department of Agriculture – Germplasm Resource Information Network (USDA-GRIN) Soybean Germplasm Collections have white flowers and are the second dominant accessions after the purple-flowered accessions. Earlier studies have shown that the w1 recessive allele of the W1 gene encoding flavonoid 3′, 5′-hydroxylase produces white flowers. In the present study, we aimed to understand why the white-flowered accessions have become abundant among the cultivated soybeans and what their genetic and regional origin is. For this purpose, 99 landraces with white flowers and 39 landraces with purple flowers from eight Asian countries and Russia were analysed with regard to the nucleotide sequences of the W1 locus. We not only found that the w1 alleles of the 99 white-flowered landraces were identical to those of the white-flowered Williams 82, but also found that these w1 alleles displayed no polymorphism at all. By carrying out a phylogenetic analysis, we were able to identify a group with W1 alleles from which the w1 allele might have diverged.